Lower bounds for the volume of the image of a ball - Klishchuk, Bogdan; Salimov, Ruslan (Ukrains’kyi Matematychnyi Zhurnal, 2023)
We consider ring Q-homeomorphisms with respect to p-modulus in the space R^n as p>n. We obtain a lower bound for the volume of the image of a ball under such mappings. We solve the extremal problems on minimizing of the functionals of the volume of the image of a ball and the area of the image of a sphere.